FAKTOR RISIKO KEJADIAN DIARE PADA BALITA - Sugiarto sugiarto; Subakir Pitriyani; Pitriyani Pitriyani (UIN Sumatera Utara Medan, 2019)
AbstractProblems with diarrhea are still a relatively large problem. In 2017 the number of diarrhea among toddlers in Indonesia was 40.07% and there were 21 times diarrhea outbreaks in 12 provinces, 17 districts / cities. Jambi Province in 2017 the prevalence of diarrhea in infants is 43.79%. In the city of Jambi the prevalence of diarrhea in children under five was 6.5%. This study aims to look at the risk factors for diarrhea in infants. This research is a quantitative research with case control research design. Case samples were 30 people and control samples were 60 people, the comparison of the number of cases and controls was 1: 2, then the number of samples in the study were 90 toddlers. Data collection was done by filling out questionnaires with univariate and bivariate analysis using the chi square test. The analysis showed that there was a relationship between hand washing with soap and running water (p - value = 0.013 & OR = 3,824), exclusive breastfeeding (p - value = 0,000 & OR = 5,902), nutritional status (p - value = 0,001 & OR = 6,625), Latrine Quality (p - value = 0.001 & OR = 5,035) and source of clean water (p - value = 0,009 & OR = 4,333) on the incidence of diarrhea in children under five. Variables that are at risk for the incidence of diarrhea in infants are hand washing with soap and running water, exclusive breastfeeding, nutritional status, latrine quality and clean water sourcesKeywords: risk factors; diarrhea; Children